Activating effects of elections: changes in young voters’ political engagement over the course of an election year - Eckstein, Katharina; Miklikowska, Marta; Šerek, Jan; Noack, Peter; Koerner, Astrid (Frontiers in Political Science, 2024)
Although the effects of elections and measures of direct democracy on policy outcomes have been well researched, their indirect “educative value” has received less attention, particularly in relation to political engagement of young people. This study examined the activating effect of the national elections in Germany (2009), Czech Republic (2010), and Sweden (2014) on young voters’ political engagement. Young voters (Germany: N = 388; Czech Republic: N = 196, and Sweden: N = 246) were surveyed several months before (T1), shortly after (T2), and several months after (T3) the respective national elections. For all three countries, the results revealed significant increases in political engagement during the election period, followed by significant declines after the election. The post-election declines were smaller compared to the election increases, suggesting a persistence of elections’ activating effects. With the exception of German young adults who were less engaged or first-time voters and showed higher increases in engagement during the election period, there were few interindividual differences. The findings suggest that major political events such as national elections can have activating effects on youth’s political engagement. They support the idea of the socializing value of election participation and of late adolescence and young adulthood as a window of opportunity for reaching young voters during politicized times.